Infiltrative Lipoma - Atypical Presentation in a Bitch - Ferreira, Priscila Inês; Basso Cartana, Camila; Gaspareto dos Santos , Leonardo; Lopes , Bibiana; da Silva Reinstein , Rainer; Mallmann Pozzobon , Franciéli; Kommers , Glaucia Denise; Veloso Brun , Maurício; Curvello de Mendonça Müller , Daniel (Acta Scientiae Veterinariae, 2024)
Background: Primary pelvic tumors have a less favorable prognosis when compared to long bone tumors. Infiltrative lipomas are benign neoplasms of mesenchymal origin, but with an invasive nature, in which highly differentiated adipocytes infiltrate tissues such as muscles, connective tissues, bones, peripheral nerves and spinal cord. Reports of infiltrative lipoma causing bone and joint damage are rare, so the objective of this report is to present clinical-surgical aspects and particularities involved in the treatment of a bitch, with an extensive tumoral mass in the left pelvic limb and coxofemoral and femoro-tibio-patellar joint destruction. The treatment used in search of a cure for the patient is highlighted. Case: One bitch, 1 and a half years old, not neutered, Australian Cattle, 13 kg body weight, with a history of increased volume in the left pelvic limb for approximately 1 year, was admitted at the Veterinary Hospital. The radiographic examination showed loss of delimitation of the coxofemoral joint, irregularity, and the presence of a proliferative and lytic process in the femoro-tibio-patellar portion, in addition to an increase in volume in adjacent soft tissue. A thoracic radiographic study was also carried out to search for metastases and cytological examination by fine-needle aspiration in several points of the limb, including the popliteal lymph node. Aggressive surgical treatment was based on evidence of bone destruction and existing damage to the joints. A mid-to-caudal partial hemipelvectomy was chosen, accompanied by limb amputation. To perform the surgery, a tumor-free area was identified and osteotomy was performed at three points, in the body of the proximal ilium, ischium plate, and pubic body. Due to the removal of the limb and the tumor, there was no muscle to close the pelvic wall, requiring the use of polypropylene mesh to correct the defect. The patient was discharged from the hospital after 24 h. The histopathological analysis of the limb revealed that it was an infiltrative lipoma, which showed infiltration of superficial and deep muscle tissue and marked degenerative lesions in the hip and femoro-tibio-patellar joints. In the macroscopy, the extension of the neoplastic mass was evident and when cutting, the loss of bone architecture. Radiographic images were also compatible with invasion and destruction of the bone delimitation. The patient was evaluated 10, 30, and 120 days post-operatively, and the animal presented a quick recovery. However, 161 days after surgery it was necessary to remove the polypropylene mesh due to its contamination. Discussion: Invasion of infiltrative lipoma into bones has been reported in only 3 dogs. Furthermore, due to the difficult macroscopic differentiation between infiltrative lipoma and normal tissue, the reported recurrence rate after surgical resection varies between 36 and 50%. Hemipelvectomy is a radical surgical procedure indicated for the management of tumors and functional abnormalities involving the pelvis or adjacent soft tissue. In canine patients diagnosed with infiltrative lipoma, surgery is reported to increase life expectancy. In studies, median survival time of 4 patients was 940 days and 13 dogs treated with cobalt radiation 60, of which 10 also underwent cytoreductive surgery, survived from 6 to 94 months. The patient in the current report survived for 21 months after the postoperative period, which is in agreement with the researchs. A case of atypical infiltrative lipoma and consequent joint destruction was highlighted in this work. However, partial hemipelvectomy was effective in the treatment, curing the alteration, despite contamination of the mesh which led to the need for surgical intervention. Keywords: surgery, complications, hemipelvectomy, polypropylene mesh.